2006
DOI: 10.1246/cl.2006.224
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS Studies about the Sorption of Cadmium Ions on Montmorillonite

Abstract: We investigated local structures around cadmium (Cd) sorbed on montmorillonite at various pH values by EXAFS (extend X-ray absorption fine structure). We found two sorption types, an outer-sphere complex and a surface precipitate. The outer-sphere complex was mainly formed at a lower pH which had an identical structure to aqueous Cd 2þ , while the surface precipitate was found at high pH which had a one-layerCadmium (Cd) is a toxic heavy metal that results in significant pollution of many soil and groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Table 2 shows that the entropy of Cd adsorption on Mont is negative (−14.7 J/mol/K), indicative of outer-sphere adsorption. Similar outer-sphere Cd-complex on pure montmorillonite is also confirmed by EXAFS data at pH ≈ 5 13 . However, the entropy for Cd adsorption on Mont-HA is slightly positive (9.8 J/mol/K), indicative of inner-sphere adsorption.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Table 2 shows that the entropy of Cd adsorption on Mont is negative (−14.7 J/mol/K), indicative of outer-sphere adsorption. Similar outer-sphere Cd-complex on pure montmorillonite is also confirmed by EXAFS data at pH ≈ 5 13 . However, the entropy for Cd adsorption on Mont-HA is slightly positive (9.8 J/mol/K), indicative of inner-sphere adsorption.…”
Section: Resultssupporting
confidence: 75%
“…3a . The first and second oscillations of the three spectra show no much difference, which is due to the same first coordination shell atoms, i.e., O atoms, seen eleswhere 13 32 33 . A few differences are pronounced at k -values of 6–10 Å −1 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…45 Extended X-ray absorption fine structure (EXAFS) studies also provide valuable information regarding the local structure of an interfacial species. EXAFS studies have been carried out on cadmium sorbed to montmorillonite, 47 cryptomelane (KMn 8 O 16 ), 48 goethite, 49 and hydrous ferric oxide. 50 These studies indicate Cd sorption can occur through outer-sphere complexation, inner-sphere complexation, or surface precipitation, and the exact mechanism of binding was reported to depend on the chemical identity of the substrate, the bulk solution pH, and the electrolyte and metal ion concentration.…”
Section: Introductionmentioning
confidence: 99%
“…An example on the use of this technique is provided by the interaction of cadmium(II) solution with thiol-functionalised 2:1 clay minerals where cadmium was found to give monomer complexes or CdO molecules on the surfaces or interlayers of the untreated clay minerals with Cd-O distance of 2.24Á while Cd-S clusters were formed on the thiol-functionalised clay minerals [3]. However earlier EXAFS studies about cadmium sorption on montmorillonite revealed outer sphere complex formation at lower pH and surface precipitate at higher pH as Cd 5 (OH) 18 (NO 3 )(H 2 O)-like structures [12]. In the study of mercury(II) interaction with goethite surface [13] the distance between the adsorbed mercury and the two closest oxygen atoms in the mineral was found to be 2.04Á and the distance between Hg and Fe was 3.28Á giving ∠ Fe-O-Hg = 108 • .…”
Section: Introductionmentioning
confidence: 99%